1987
DOI: 10.1002/ajim.4700110605
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function and intradermal tests in workers exposed to soft‐paper dust

Abstract: A survey was carried out in the processing department of a paper mill, consisting of environmental and personal monitoring, a short questionnaire concerning chronic non-specific lung disease (CNSLD), spirometry, and intradermal tests. Spirometry was performed on Monday, Wednesday, and Friday. Exposures to paper dust regularly exceeded the Dutch Maximal Allowable Concentrations (MACs) for total and respirable dust. There were indications of a qualitatively different exposure to molds inside the mill in comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Previous studies among soft-paper workers have demonstrated a decreased lung function (Heederik et al 1987;Ericsson et al 1988) and an increased mortality because of obstructive lung disease (Thore n et al 1989b). The observed increased prevalence of wheezing, despite possible selection bias, indicates an increased risk of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies among soft-paper workers have demonstrated a decreased lung function (Heederik et al 1987;Ericsson et al 1988) and an increased mortality because of obstructive lung disease (Thore n et al 1989b). The observed increased prevalence of wheezing, despite possible selection bias, indicates an increased risk of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Industry-or occupation-specific studies of organic/ biological dust Of the industry-or occupation-specific studies of organic/ biological dust exposure and COPD (table 3), nine (72)(73)(74)(75)(76)(77)(78)(79)(80) were cross-sectional and ten (81)(82)(83)(84)(85)(86)(87)(88)(89)(90) longitudinal with follow up-time between 1-20 years. A majority of the studies came from Europe (72-77, 79, 80, 85, 86, 88) and the US (82,83,89,90), with two each from China (81,84) and South Africa (78,87).…”
Section: Population-based Studiesmentioning
confidence: 99%
“…The studies comprised a total of 16 856 subjects with exposures of cotton, flax, jute, farming, grain, wood, paper, and rubber. In eight of the studies (75,77,78,80,(86)(87)(88)(89), personal sampling technique was used to define the exposure; in one study (72), both personal and area-level sampling techniques were used, and in five studies (79,81,82,84,90), arealevel sampling techniques alone were used. The exposure was characterized by questionnaire in four studies (73,74,76,83), while in one study (85) employee records defined exposure.…”
Section: Population-based Studiesmentioning
confidence: 99%
“…Soft paper is a semimanufactured product which is further processed (converted) to toilet paper, paper towels, and napkins. Impairments in lung function have been observed among heavily exposed workers [Heederik et al, 1987;Ericsson et a]., 1988;Jiiwholm et al, 19881. An increased prevalence of respiratory symptoms among exposed workers, as well as an increased mortality due to obstructive lung disease, have also been found [Ericsson et al, 1988;Thorh et al, 1988, 19891.…”
Section: Introductionmentioning
confidence: 99%